1991
DOI: 10.1177/00220345910700030101
|View full text |Cite
|
Sign up to set email alerts
|

Protection of Rats Against Dental Caries by Passive Immunization With Hen-egg-yolk Antibody (IgY)

Abstract: Hen-egg-yolk antibody (IgY) was prepared against Streptococcus mutans MT8148 serotype c that was cultivated in medium containing sucrose, and it was used in passive caries-immunity studies. Specific pathogen-free rats infected with S. mutans MT8148 (c) and fed with a cariogenic diet containing more than 2% immune yolk powder developed significantly lower caries scores than did the ones infected with the same strain and fed with a diet containing only control yolk powder obtained from non-immunized hens. Simila… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
62
2
1

Year Published

1993
1993
2017
2017

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 25 publications
4
62
2
1
Order By: Relevance
“…Research conducted by Paau and Rong-Jiang [21] in 2006 showed that the IgY-anti-S. mutans toothpaste decreased the percentage of S. mutans among the total anaerobic bacteria found in both saliva and plaque samples. Similar to previous research, Otake et al [22] used anti-S. mutans whole-cell IgY in the form of frozen egg yolk in the rat diet. However, the colony count of S. mutans was not significantly different after this intervention.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…Research conducted by Paau and Rong-Jiang [21] in 2006 showed that the IgY-anti-S. mutans toothpaste decreased the percentage of S. mutans among the total anaerobic bacteria found in both saliva and plaque samples. Similar to previous research, Otake et al [22] used anti-S. mutans whole-cell IgY in the form of frozen egg yolk in the rat diet. However, the colony count of S. mutans was not significantly different after this intervention.…”
Section: Introductionmentioning
confidence: 83%
“…Wen et al [27] reported that IgY was capable of impeding glucan synthesis by S. mutans and S. sobrinus. However, several of these studies did not use gel as a clinical application medium, instead relying on mouthwash or food and toothpaste [21,22]. Compared with mouthwash, pure IgY is dissolved in 10 ml of water [20].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Administration of IgY against S. mutans CA-GTase specifically inhibited insoluble glucansynthesizing CA-GTase, resulting in a significant reduction in the development of dental caries. Otake et al (1991) reported that anti-S. mutans CA-GTase IgY suppressed development of dental carries in rat model [42]. Hatta et al (1997) reported that the effectiveness of IgY with specificity to S. mutans prevented the colonization of mutans streptococci in the oral cavity of humans [43].…”
Section: Anti-streptococcus Mutans Igymentioning
confidence: 99%
“…Regular consumption of Tea and Coffee have been reported by Matheson et al (2011) to be associated with a likelihood of lower MRSA nasal carriage and thereby recommending it as a new, safe, inexpensive and easily accessible method to decrease MRSA nasal carriage. Tea contains substances with antimicrobial potentials such as caffeine, theobromine, xanthine and tannic acid (Elvin-Lewis et al, 1980;Otake et al, 1991). Toda et al (1989) reported the antimicrobial effect of coffee on Staphylococcus aureus, Salmonella typhi, Shigella dysentariae, Vibrio cholera, Vibrio parahaemolyticus and Yersinia enterolitica and attributed the bactericidal effect to the presence of tannic acid.…”
Section: Introductionmentioning
confidence: 99%